Issues of Static and Dynamic Graphical Testing of Stochastic Transformations Results - Prokofiev, Anton O.; Chirkin, Andrey V.; Stepanov, Maxim M.; Chugunkov, Ilya V. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2021)
The article deals with the pseudorandom number generators exploration using graphical methods. In this paper, we defined the necessary tools for building graphical tests and consider the features of static and dynamic PRNG research methods. Also, a method presented for numerical sequences visual inspection based on the joint use of the methods considered in this paper. Additionally, we presented comparison of the stochastic transformations results exploration using static and dynamic methods. Finally, we outline ways to improve the stochastic transformations research quality.